2017
DOI: 10.1038/s41598-017-13691-8
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting Strong and Weak Single-Walled Carbon Nanotubes Interactions with Mitochondrial Voltage-Dependent Anion Channels Using Molecular Docking and Perturbation Theory

Abstract: The current molecular docking study provided the Free Energy of Binding (FEB) for the interaction (nanotoxicity) between VDAC mitochondrial channels of three species (VDAC1-Mus musculus, VDAC1-Homo sapiens, VDAC2-Danio rerio) with SWCNT-H, SWCNT-OH, SWCNT-COOH carbon nanotubes. The general results showed that the FEB values were statistically more negative (p < 0.05) in the following order: (SWCNT-VDAC2-Danio rerio) > (SWCNT-VDAC1-Mus musculus) > (SWCNT-VDAC1-Homo sapiens) > (ATP-VDAC). More negative FEB value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…It does not have a remarkable weight on the FEB dock the Ligand-total dimensionality (total DOF = 3 + 4 + n) due to the very small intra-molecular contributions of force ield parameters of the laccase-ligand. These are considered as rigid and taking account the ligand-geometry optimization (described above) [43] based on the ΔG internal minimization of all the laccaseligands used in the present study.…”
Section: Evaluation Of Laccase-ligand Complexes Interactionsmentioning
confidence: 99%
“…It does not have a remarkable weight on the FEB dock the Ligand-total dimensionality (total DOF = 3 + 4 + n) due to the very small intra-molecular contributions of force ield parameters of the laccase-ligand. These are considered as rigid and taking account the ligand-geometry optimization (described above) [43] based on the ΔG internal minimization of all the laccaseligands used in the present study.…”
Section: Evaluation Of Laccase-ligand Complexes Interactionsmentioning
confidence: 99%
“…Studies focused on NM-induced biological effects on K + and Na + channels are summarized in Table 1. (Chhowalla et al, 2005;Gonzalez-Durruthy et al, 2017;Park et al, 2003) of ion channels in many directions by (A) directly blocking the channel pore from extracellular sites, (B) binding to hydrophobic residues in extracellular and intracellular sites or (C) penetrating into the lipid bilayer of the cell membrane, and (D) causing the rotation of functional areas, such as voltage sensor domains (VSDs). The structure and function of ion channels are affected by these interactions (Gu et al, 2018), leading to partial or complete block of current (Calvaresi, Furini, Domene, Bottoni, & Zerbetto, 2015;Kraszewski, Tarek, Treptow, & Ramseyer, 2010).…”
Section: The Effects Of Interactions Between Nms and Ion Channelsmentioning
confidence: 99%
“…Chloride channels have many important physiological roles, including pH regulation, volume homeostasis, organic solute transport, cell migration, cell proliferation, and cell differentiation (Jentsch, Stein, Weinreich, & Zdebik, 2002). However, only a few studies have shown that exposure to NMs could affect the function of Cl − channels (Ahmad et al, 2012;Gonzalez-Durruthy et al, 2017). A molecular docking simulation suggested that three types of single-walled carbon nanotubes (SWCNTs) can block the mitochondrial voltage-dependent anion channel (Gonzalez-Durruthy et al, 2017).…”
Section: Other Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a brand new method for data fusion in nanotechnology, bio-molecular sciences, chemistry and big data analysis has been proposed in different works: it integrates Perturbation Theory (PT) and Machine Learning (ML) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], using distinct PT operators to analyze changes in the varied non-structural and structural conditions of a test at once (PTML). A few of these PT operators represent the generalization of a classic cheminformatics approach introduced by Corwin Hansch [ 14 ].…”
Section: Introductionmentioning
confidence: 99%